Monitoring of Eutrophication of Lakes in Volyn Polissya (on the example of Lake Turske) - Fesyuk, Vasyl O.; Moroz, Iryna; Fedonyuk, Mykola A.; Polianskyi, Serhiy V. (My University, 2025)
The article considers of example of studying the current state of eutrophication for one of the lakes of Volyn Polissya (Turske Lake) using modern remote sensing methods. Eutrophication causes significant damage to the ecosystems of the Volyn Polissya lakes. The use of the Normalized Difference Vegetation Index (NDVI) and the Normalized Difference Algae Index (NDAI) allowed us to find out the peculiarities of the development of eutrophication processes in the lake in different years. The use of statistical methods of analysis made it possible to assess the closeness of the relationship between the weighted values of NDVI and the water surface temperature of Lake Turske. It has been established that the intra-annual variation of the NDVI and NDAI indices is characterized by an increase from May to August and a further decrease in values by the end of the year. Among the factors affecting the level of eutrophication, the most important are water temperature, nutrient supply (phosphorus, nitrogen) and morphological features of water bodies (area, depth, volume, shape of the basin).
Keywords: Lake; Turske Lake; Volyn Polissya; Volyn region; Monitoring; Monitoring of eutrophication